Analisis Dan Perancangan Sistem Pendukung Keputusan Penerima Program Bantuan Stimulan Perumahan Swadaya Dengan Simple Additive Weighting Pada Dinas Perumahan Dan Kawasan Permukiman Kabupaten Batang Hari - Putri, Selviany; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2020)
The Batang Hari Regency Housing and Settlement Area Office continues to reduce the number of uninhabitable homes through the Self-Help Housing Stimulant Assistance Program (BSPS). In selecting / selecting potential recipients of assistance it takes a long time because it has not been properly systemized. The purpose of this study is to analyze and design a decision support system for recipients of self-help housing stimulant programs in the Housing and Settlement Area of Batang Hari Regency by identifying its weaknesses and then analyzing the needs of the decision support system so that later it can help the head of the office to be taken into consideration in determine the recipient of the BSPS program.